2018
DOI: 10.3390/antiox7070082
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Memory Dysfunction Induced by Vitamin C Deficiency Is Associated with Changes in Monoaminergic Neurotransmitters and Aberrant Synapse Formation

Abstract: Vitamin C (vitC) is important in the developing brain, acting both as an essential antioxidant and as co-factor in the synthesis and metabolism of monoaminergic neurotransmitters. In guinea pigs, vitC deficiency results in increased oxidative stress, reduced hippocampal volume and neuronal numbers, and deficits in spatial memory. This study investigated the effects of 8 weeks of either sufficient (923 mg vitC/kg feed) or deficient (100 mg vitC/kg feed) levels of dietary vitC on hippocampal monoaminergic neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Several preclinical studies have illustrated the importance of vitC in early development, in particular that of the brain and cognition [60,63,98,99,100]. In humans, studies have shown that poor maternal vitC status results in increased fetal oxidative stress, impaired implantation and increased risk of complications including preeclampsia [101,102].…”
Section: Factors Affecting Vitamin C Homeostasis and Requirementsmentioning
confidence: 99%
“…Several preclinical studies have illustrated the importance of vitC in early development, in particular that of the brain and cognition [60,63,98,99,100]. In humans, studies have shown that poor maternal vitC status results in increased fetal oxidative stress, impaired implantation and increased risk of complications including preeclampsia [101,102].…”
Section: Factors Affecting Vitamin C Homeostasis and Requirementsmentioning
confidence: 99%
“…There was no apparent effect on SOD, GSH or MDA levels in the brain, suggesting that the effects of deficiency could be due to mechanisms not directly associated with oxidative stress [185]. In agreement with an effect on more specific functions, reduced levels of synaptophysin and alterations in serotonin metabolites in the hippocampus of deficient animals suggested impaired neuronal signal transmission, potentially exacerbating the consequences of the lower neuronal numbers [266].…”
Section: Changes In Brain Structure and Functionmentioning
confidence: 74%
“…Reduced spatial memory competence. [185,266] BDNF: brain-derived neurotrophic factor; deficiency: low vitC supplementation; depletion: no vitC supplementation; GSH: glutathione; MDA: malondialdehyde; PD: postnatal day; SOD: superoxide dismutase; wks: weeks.…”
Section: Changes In Brain Structure and Functionmentioning
confidence: 99%
“…Antioxidants contribute to the protection of nerve cells from damage and improve neurotransmitter function, which can help prevent and treat depression. Specifically, the antioxidant vitamin C has been found to promote the release of neurotransmitters such as dopamine, norepinephrine, and 5-hydroxytryptamine from neurons, increasing the levels of neurotransmitters that influence communication between neurons 58 . The fifth is the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%